Severe adverse effects of bromocriptine in lactation inhibition: a pharmacovigilance survey. (11th March 2015) - Bernard, N; Jantzem, H; Becker, M; Pecriaux, C; Bénard‐Laribière, A; Montastruc, JL; Descotes, J; Vial, T; the French Network of Regional Pharmacovigilance Centres
<x xml:space="preserve">Abstract</x> Objective To assess the nature and conditions of the occurrence of adverse drug reactions (ADRs) of bromocriptine, which is used to inhibit lactation. Design Observational study. Setting Cases from the French pharmacovigilance database and the marketing authorisation holders. Sample Serious ADRs reported between 1994 and 2010 in association with bromocriptine used for lactation inhibition in France. Methods Each case was checked to confirm the bromocriptine indication, the seriousness of the ADR, the modalities of bromocriptine use, and to identify possible associated predisposing factors. Main outcome measures Number and description of serious ADRs, with a particular focus on misuse and associated predisposing factors. Results Among 105 serious ADRs, including two fatal cases, the most frequent were cardiovascular (70.5%), neurological (14.3%), and psychiatric (8.6%) disorders. Cardiovascular disorders primarily consisted of ischaemic manifestations (n = 47): acute ischaemic stroke (n = 18, one death), myocardial infarction (n = 11, one death), and reversible postpartum cerebral angiopathy (n = 10). Misuse was identified in 52 cases (70.3%) of cardiovascular disorders, and mostly consisted of bromocriptine continuation despite the occurrence of first symptoms suggesting an ADR or the absence of a progressive titration of bromocriptine. About half of these women had cardiovascular predisposing factors, mainly tobacco smoking, overweight or obesity, or a history of hypertension or pre‐eclampsia. Conclusions This survey, together with published data, provides further evidence that serious ADRs still occur after bromocriptine use in lactation inhibition, and that most of these ADRs could have been avoided. The use of bromocriptine should therefore be limited to cases where no other options are available to inhibit lactation.